Les irréguliers du Langage. - Jago-Antoine, Véronique; Quaghebeur, Marc (Sevilla : Casa Museo Murillo, 1992)
Alechinsky, Pierre ; Van Anderlecht, Englebert ; Brenta, Gilles ; Broodthaers, Marcel ; Bury, Pol ; Calonne, Jacques ; Cordier, Pierre ; De Coster, Charles ; Delahaut, Jo ; Devolder, Eddy ; Dotremont, Christian ; Droste, Monica ; Dutrieux, Daniel ; Dypréau, Jean ; Ensor, James ; Gailliard, Jean-Jacques ; gaverol, Jane ; Gutt, Tom ; Hergé ; Joostens, Paul ; Keguenne, Jacques ; van Kessel, Françoise ; Lennep, Jacques ; Magritte, René ; Mandelbaum, Stéphane ; Mariën, Marcel ; Mesens, E.L.T. ; Michaux, Henri ; Mineur, Michel ; Noiret, Joseph ; Nougé, Paul ; Octave, Jean-François ; Peyo (Culliford, Pierre) ; Polackova, Maja ; Raine, Jean ; de Regoyos, Dario ; Rombouts, Guy ; Rops, Félicien ; Roulin, Félix ; Scutenaire, Louis ; Seuphor, Michel ; Silvain, Christian ; De Taeye, Camille ; Tondeur, Francis ; Vandercam, Serge ; Verhaeren, Emile ; Verheggen, Jean-Pierre ; Vinche, Lionel ; Willems, Robert ; Willems, Suzanne ; de Wouwer, Roger van
Frans & Spaans
Les irréguliers du Langage, Casa Museo Murillo, Sevilla, 24 Septiembre - 29 Noviembre 1992
boek